Microstructure of Compacted Graphite Iron Near Critical Shrinkage Areas in Cylinder Blocks - Ramos A.K.* (2020)
© 2020, American Foundry Society.To study the microstructure of CGI near areas prone to shrinkage, a special sample was developed that resembles critical areas in cylinder blocks. Foundry trials were conducted with different magnesium contents and inoculation amounts. Using color etching techniques to follow the solidification sequence, four areas were observed with different macrostructure: (i) direct chill and columnar region near the surface; (ii) small eutectic cells and small intercellular space; (iii) large eutectic cells and large intercellular space; and (iv) eutectic cells with carbides in the last to freeze area. By increasing the amount of inoculation, the size of the eutectic cells in the zone with large eutectic cells (iii) is reduced, and the eutectic cells are now smaller and more evenly distributed through the section. Increasing the magnesium content brings a similar effect. In zone (iv), the samples with less inverse chill formation show smaller shrinkage porosities, which are located in the same regions where the inverse chill are, between the eutectic cells, in the last to freeze areas; they also have higher amounts of spheroidal graphite in the last-to-freeze areas. The amount of inverse chill carbides observed in zone (iv) did not present any clear relation with inoculation levels or magnesium content variations used in the experiments.